Population pharmacokinetic and pharmacodynamic analysis to support treatment optimization of combination chemotherapy with indisulam and carboplatin - Zandvliet, Anthe S (Blackwell Science Inc, 2008)
AIMS: Indisulam and carboplatin have shown synergistic activity in preclinical studies. In a dose escalation study of the combination, a treatment delay was frequently required in a 3-weekly regimen to allow recovery from myelosuppression from previous cycles. A 4-weekly regimen was better tolerated, but had a decreased dose-intensity which may compromise efficacy. The aims of this study were (i) to develop a pharmacokinetic–pharmacodynamic (PK–PD) model to describe the myelosuppressive effect of the combination, and (ii) to use this model to select a dosing regimen for Phase II evaluation. METHODS: Sixteen patients were treated at four different dose levels of indisulam (1-h infusion on day 1) and carboplatin (30-min infusion on day 2). Pharmacokinetic data were analysed with nonlinear mixed effects modelling. A semiphysiological model describing chemotherapy-induced myelosuppression characterized the relationship between the pharmacokinetics and the haematological toxicity of indisulam and carboplatin. A simulation study was performed to evaluate the tolerability and dose-intensity for 3-weekly and 4-weekly treatment regimens. RESULTS: The PK–PD model described the pharmacokinetics and the myelosuppressive effect of indisulam and carboplatin. The risk of a treatment delay at cycle 2 due to myelosuppression was unacceptably high (34–65%) in a 3-weekly regimen for various dose levels (350–600 mg m(−2) indisulam in combination with carboplatin to achieve an AUC of 4–6 mg min(−1) ml(−1)). This risk was acceptable for a 4-weekly regimen (9–24%), which is in line with the clinical study results. CONCLUSIONS: This PK–PD study supports the selection of indisulam 500 mg m(−2) and a dose of carboplatin to achieve an AUC of 6 mg min(−1) ml(−1) in a 4-weekly regimen as the recommended dose for future studies.